2012
DOI: 10.4236/gsc.2012.21001
|View full text |Cite
|
Sign up to set email alerts
|

Styrene Epoxidation in Aqueous over Triazine-Based Microporous Polymeric Network as a Metal-Free Catalyst

Abstract: Tirazine based microporous polymeric (TMP) network was found to be an efficient metal-free catalyst for the epoxidation of styrene. The reactions were performed in water as an environmentally benign medium using H 2 O 2 as a green oxidant at ambient temperature. The reaction afforded higher yield with 90% conversion of styrene and 98% selectivity to styrene oxide in 6 h. The triazine based microporous polymeric network can be readily recovered and reused up to 4 cycles without significant loss in catalytic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…For PAN-MP, the steric hindrance of methyl groups is disadvantageous for the formation of homogeneous hyper-cross-linked structure, as reflected in its broader WAXD diffractive halo compared to that of PAN-P (Figure S1, Supporting Information), which results in a reduction of specific surface area and loss of pore volume to some extent. In contrast to PAN-P and PAN-MP, the fluorinated PAN-FP and PAN-FMP show the significantly larger BET surface areas of 703 and 907 m 2 g –1 , respectively, which are at a moderate level comparable to those earlier reported polyaminal frameworks (479–1377 m 2 g –1 ). The high electronegativity of fluorine atoms effectively enhances the reactivity of aromatic aldehyde and facilitates the formation of hyper-cross-linked structure to generate large amount of pores. In addition, it is noteworthy that PAN-FMP possesses the largest surface area and porous volume among the four polymers, meaning that the strong electron-withdrawing effect of trifluoromethyl plays a more significant role in the formation of porous structure although it also has the steric hindrance similar to methyl in PAN-MP.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…For PAN-MP, the steric hindrance of methyl groups is disadvantageous for the formation of homogeneous hyper-cross-linked structure, as reflected in its broader WAXD diffractive halo compared to that of PAN-P (Figure S1, Supporting Information), which results in a reduction of specific surface area and loss of pore volume to some extent. In contrast to PAN-P and PAN-MP, the fluorinated PAN-FP and PAN-FMP show the significantly larger BET surface areas of 703 and 907 m 2 g –1 , respectively, which are at a moderate level comparable to those earlier reported polyaminal frameworks (479–1377 m 2 g –1 ). The high electronegativity of fluorine atoms effectively enhances the reactivity of aromatic aldehyde and facilitates the formation of hyper-cross-linked structure to generate large amount of pores. In addition, it is noteworthy that PAN-FMP possesses the largest surface area and porous volume among the four polymers, meaning that the strong electron-withdrawing effect of trifluoromethyl plays a more significant role in the formation of porous structure although it also has the steric hindrance similar to methyl in PAN-MP.…”
Section: Resultsmentioning
confidence: 64%
“…The condensation of aromatic multialdehyde with triamine melamine has been successfully employed to prepare hyper-cross-linked microporous polyaminal networks. In this case, the intermediate imine bond (−CN−) generated further reacts with the active amino group to eventually form stable aminal linkage (−NH–CH–NH−). It is rational to deduce from the above studies that the polymerization between melamine and monoaldehyde compounds would also give rise to hyper-cross-linked polyaminal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microporous polyaminals are a newly emerged class of porous organic polymers that are synthesized from triazine-based multiamines using various aldehydes. Recently, it was found that formamide, formohydrazide, N -methylformamide, and N , N -dimethylformamide can also be utilized as starting monomers to prepare microporous polyaminals through a simple one-step solution polycondensation reaction without using any catalyst. , Besides the large surface area and high porosity, the abundant nitrogen elements stemming from the triazine rings and aminal linkages lead to the strong affinity of the polyaminal skeleton for CO 2 gas. In the past few years, the applications of microporous polyaminals in CO 2 capture, absorption of volatile iodine, , catalysis, and detection of toxic pesticides , have been reported in the literature. Nevertheless, the adsorption of C 1 –C 3 light organic hydrocarbons in porous polyaminals, focusing on the separation of different components in natural gas, has not been studied up to now.…”
Section: Introductionmentioning
confidence: 98%
“…Park et al. demonstrated the catalytic applications of melamine–terephthalaldehyde polymer (SNW1, Figure 1) in styrene epoxidation14a and Knoevenagel condensation14b reactions. Recently, we reported the synthesis of triazine‐based mesoporous covalent imine polymers as novel supports for the copper‐mediated Chan–Lam cross‐coupling N ‐ arylation reaction15a and palladium nanoparticles supported on triazine‐functionalized mesoporous covalent organic polymers as efficient catalysts for the Mizoroki–Heck cross‐coupling reaction 15b.…”
Section: Introductionmentioning
confidence: 99%